Different responses of tumor and normal cells to low-dose radiation - Yu, Hongsheng; Liu, Ning; Wang, Hao; Shang, Qingjun; Jiang, Peng; Zhang, Yuanmei (Contemporary Oncology/Współczesna Onkologia, 2013)
Aim of the study: We demonstrated stimulation of both erythrocyte immune function and superoxide dismutase activity in tumor-bearing mice in response to whole-body 75 mGy X-rays. In addition, we enhanced the chemotherapeutic effect by exposing tumor-bearing mice to low-dose radiation (LDR). This study aims to investigate the different responses of tumor cells and normal cells to LDR. Material and methods: Survival fraction, micronucleus frequency, and cell cycle of Lewis cells and primary human fibroblast AG01522 cells were measured. S180 sarcoma cells were implanted in mice, and tumor sizes were measured in vivo . Results : In response to LDR exposure in vitro , a stimulating effect was observed in AG01522 cells but not in Lewis cells. Low-dose radiation did not cause an adaptive response in the Lewis cell cycle. Lack of an LDR-induced radioadaptive response in tumor cells was observed in tumor-bearing mouse models. Furthermore, a higher apoptotic effect and lower expression of the anti-apoptosis gene Bcl-2 were found in tumor cells of tumor-bearing mice exposed to D1 + D2 than those in tumor cells of tumor-bearing mice exposed to D2 alone. Conclusions : Different responses of tumor cells and normal cells to LDR were found. Low-dose radiation was found to stimulate the growth of normal cells but not of tumor cells in vitro and in vivo , which is a very important and clinically relevant phenomenon.